PENGUASAAN MATERI PEMBELAJARAN KETERAMPILAN BERBAHASA INDONESIA MAHASISWA S1 PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNIVERSITAS BENGKULU - Nafri Yanti; Suhartono Suhartono; Rio Kurniawan (Universitas Bengkulu, 2018)
The purpose of this study is to describe the mastery of Indonesian language skills learning material of Indonesian Language Education Study Program of Teacher Training and Education Faculty of Bengkulu University in 2016. The specific purpose of this research is to describe the mastery of learning material of listening, speaking, reading and writing skills student of Indonesian Language and Literature Education Study Program FKIP UNIB. The method used in this research is quantitative research method. Based on the results of the study, its noted that the mastery of learning materials of Indonesian Language Skills on Undergraduate Studies Program Language and Literature Indonesia FKIP UNIB is still relatively low. The results showed that students who have a very good understanding of the category of learning skills of Indonesian language is only 10% of the overall research object. Students who have a good understanding of the category of learning skills of Indonesian language skills as much as 24%. The number of students who have sufficient mastery of the subject matter of Indonesian language skills occupies the dominant percentage with 45%. Students in the category have less mastery of Indonesian language skills learning materials as much as 16%. While 5% of students fall into the category of having knowledge that is still less once for learning materials Indonesian skills. Students should have a better mastery of learning materials in Indonesian language skills as a basic capital to teach Indonesian subjects, especially at junior and senior high schools. Therefore in the future it is expected to do more effective learning process improvement related to Indonesian language skills learning materials, so that students' mastery of learning materials of Indonesian language skills will be better. Keywords: mastery, learning materials, speech skills